Pengembangan Algoritma Vigenere Cipher Berbasis Kunci Dinamis Dalam Pengamanan Pesan Teks - Munjiat Setiani Asih; Rismayanti Rismayanti; M Imam Fadhlurahman; Ade Zulkarnain Hasibuan (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
This research aims to develop a dynamic key-based Vigenère Cipher algorithm as a solution to improve the security of text messaging. Vigenère Cipher is one of the classical cryptographic methods that has a weakness against frequency analysis, especially when the key used is static. In this study, we propose a new approach by implementing a dynamic key that changes every time a message is sent. This dynamic key is generated through a pseudorandom algorithm that considers the time of transmission and the characteristics of the message. The research methodology includes analyzing cryptography theory, algorithm implementation, and testing the effectiveness and efficiency in encrypting and decrypting messages. The test results show that the developed algorithm not only improves message security through higher key complexity, but also maintains the speed of encryption and decryption processes. In addition, analysis of various message delivery scenarios shows that the algorithm is able to overcome frequency analysis attacks that are often a threat in traditional cryptographic methods. With these results, this research makes a significant contribution to the development of more secure and practical text message security systems, and opens up opportunities for further applications in the field of modern cryptography.